Model Matematika Penyebaran Penyakit Tungro pada Tanaman Padi dengan Vektor Wereng Hijau Nephotettix virescens - Dwi Shinta Kumala Ningsih; Dewi Murni (Journal of Mathematics UNP, 2021)
Tungro is a disease of rice plants caused by Rice Tungro Spherical Virus (RTSV) and Rice Tungro Bacilliform Virus (RTBV). The green leafhopper Nephotettix virescens is a vector of this disease. The purpose of this study was to determine the form of a mathematical model of the spread of tungro disease by using predators to control its spread and interpret the results of the analysis. The form of the mathematical model is SEI-SIP. This research is a basic or theoretical research. The results of model analysis obtained two fixed points free of disease and two fixed points endemic to spread of tungro. The stability analysis resulted in R_0 which interpreted that the high rate of disease transmission, vector suction power and the transition rate from exposed to infected would result in an outbreak of disease, low predator mortality and high predation rates would reduce the spread of tungro